2018
DOI: 10.3390/ma11040465
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Alternating Current Interference and Cathodic Protection on Pitting Corrosion and Stress Corrosion Cracking Behavior of X70 Pipeline Steel in Near-Neutral pH Environment

Abstract: Influence of alternating current (AC) on pitting corrosion and stress corrosion cracking (SCC) behavior of X70 pipeline steel in the near-neutral pH environment under cathodic protection (CP) was investigated. Both corrosion and SCC are inhibited by −0.775 VSCE CP without AC interference. With the superimposition of AC current (1–10 mA/cm2), the direct current (DC) potential shifts negatively under the CP of −0.775 VSCE and the cathodic DC current decreases and shifts to the anodic direction. Under the CP pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
(59 reference statements)
3
15
0
Order By: Relevance
“…When the applied CP level was −0.925 V vs. CSE (data not shown), the DC potential becomes more positive at low AC densities of 10 and 50 A•m −2 , while it decreases with 100 A•m −2 AC density. Recently, Wang et al [55] reported similar conclusions for X70 steel in near-neutral bicarbonate solution: at −0.775 V vs. SCE, the DC potential is shifted negatively consequently to the application of AC, while at −0.95 V vs. SCE and −1.2 V vs. SCE, an increase of DC potential is measured (Figure 3). In this case, the potential variation is proportional to AC density.…”
Section: Effect On DC Potential (Cathodic Protection Condition)supporting
confidence: 65%
See 2 more Smart Citations
“…When the applied CP level was −0.925 V vs. CSE (data not shown), the DC potential becomes more positive at low AC densities of 10 and 50 A•m −2 , while it decreases with 100 A•m −2 AC density. Recently, Wang et al [55] reported similar conclusions for X70 steel in near-neutral bicarbonate solution: at −0.775 V vs. SCE, the DC potential is shifted negatively consequently to the application of AC, while at −0.95 V vs. SCE and −1.2 V vs. SCE, an increase of DC potential is measured (Figure 3). In this case, the potential variation is proportional to AC density.…”
Section: Effect On DC Potential (Cathodic Protection Condition)supporting
confidence: 65%
“…Materials 2020, 13, x FOR PEER REVIEW 7 of 21 et al [55] reported similar conclusions for X70 steel in near-neutral bicarbonate solution: at −0.775 V vs. SCE, the DC potential is shifted negatively consequently to the application of AC, while at −0.95 V vs. SCE and −1.2 V vs. SCE, an increase of DC potential is measured (Figure 3). In this case, the potential variation is proportional to AC density.…”
Section: Effect On DC Potential (Cathodic Protection Condition)supporting
confidence: 56%
See 1 more Smart Citation
“…where R Corr (millimeters/year), E W (equivalent weight/grams), ρ (density of the metal or alloy/(g/cm 3 )), and j Corr (µA/cm 2 ). It has been reported that the reaction of cathode for metals and/or alloys in neutral chloride solutions is the reduction of O 2 as per the following equation [26,27];…”
Section: Cpp Measurementsmentioning
confidence: 99%
“…The hardness of the test decreases with the duration of the test specimen submerged in corrosive media. [1] Research corrosion rate on carbon steel pipe API 5L-Grade B in the environment of H2S gas CO2 saturated condition in NaCl solution [6], corrosion rate on carbon steel pipe API 5L-Grade B in H2S gas environments and saturated CO2 conditions in NaCl solution and acetic acid solution [7], study of stress corrosion cracking due to sweet gas (H2S and CO2) in carbon steel pipe API 5L-X65 to corrosion rate in acetic acid solution [8], Analysis corrosion rate of Carbon steel pipe API 5L-X65 API with determination three point Method on H2S Gas Conditions Saturated conditions of CO2 in Acetic Acid Solutions [9]. Characteristics of carbon steel pipe API 5L-X65 API with three point loading Method in H2S Gas Conditions Saturated Conditions CO2 in Acetic Acid Solutions [10], Analysis of the 5L-X65 API Carbon Steel Pipes with Three Point Loading Method on H2S Gas Conditions Saturated CO2 in Acetic Acid Solution [11].…”
Section: E K S a K T A : B E R K A L A I L M I A H B I D A N G M I mentioning
confidence: 99%